2021
DOI: 10.7759/cureus.16704
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Mechanically Ventilated COVID-19 Patients With Pneumothoraces

Abstract: IntroductionPneumothoraces in mechanically ventilated patients with COVID-19 indicate severe lung damage from inflammatory injury and barotrauma. These patients have a high mortality rate, and additional factors may further alter their clinical course. MethodsWe conducted a retrospective review of patients admitted to 11 public hospitals in New York City between March 6 and April 9, 2020, diagnosed with COVID-19. We identified 39 patients who developed pneumothoraces immediately after intubation or after a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Barotrauma was a relatively common finding in patients with COVID-19 pneumonia during the pandemic, which was either P-SILI or ventilator-induced (invasive or non-invasive) [24,25]. Many researchers suggested that spontaneous pneumothorax was possible in patients with high C-reactive protein, severe lymphopenia, high D-dimer, high lactate dehydrogenase and ferritin, or high viral load [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Barotrauma was a relatively common finding in patients with COVID-19 pneumonia during the pandemic, which was either P-SILI or ventilator-induced (invasive or non-invasive) [24,25]. Many researchers suggested that spontaneous pneumothorax was possible in patients with high C-reactive protein, severe lymphopenia, high D-dimer, high lactate dehydrogenase and ferritin, or high viral load [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…All of our patients however suffered from severe ARDS due to COVID-19 pneumonia and hence severe lung inflammation, setting up an optimal environment for the pathogenesis of pneumothorax. There have been many other case reports/series, retrospective cohort studies, and meta-analyses that have highlighted this phenomenon of pneumothorax and pneumomediastinum in COVID-19 patients [1][2][3][4][5][6][7][8][9][10][11][12]. It is said that 1% of all patients develop pneumothorax with COVID-19, although almost 7.5% of patients who are admitted develop pneumothorax with a mortality rate of about 58%.…”
Section: Discussionmentioning
confidence: 99%